Lübeck's Founding Quarter: Urban Development at an Authentic Site - André Dubisch (Internet Archaeology)
Lübeck, one of the oldest Hanse cities in Germany, harbours a rich historical heritage that is particularly evident in the so-called Founding Quarter. In the years 2009–2016, archaeological investigations were carried out in an area of more than 10,000m² in the run-up to urban restructuring measures, which not only revealed the origins of the city, but also documented the unique development of the former merchants' quarter. Based on these findings, this paper examines the challenges and opportunities for contemporary urban development using the example of Lübeck's historic city centre. The former merchants' quarter can, and should in the future, be seen as a living example of the successful integration of historical heritage and modern urban planning in a United Nations Educational, Scientific and Cultural Organization (UNESCO) World Heritage Site.